LIMNOLOGICAL INVESTIGATION OF A POND OF CHAPRA DISTRICT NORTH BIHAR, INDIA WITH SPECIAL REFERENCE TO PERIPHYTON - SINGH, DHRUB KUMAR; KUMAR, PRASHANT (UTTAR PRADESH JOURNAL OF ZOOLOGY, 2009)
Present investigation is made on certain limnological parameter of a North Bihar pond with special reference to periphyton. Physico-chemical parameters were investigated for temperature, pH, Dissolved Oxygen (DO2), Free Carbon dioxide (FCO,), Total hardness (TH), Calcium hardness (CaH), Magnesium hardness (MgH), Calcium (Ca)2 and Magnesium (Mg)2 ions. They were within tolerable range. Periphyton were represented by algae and microfauna. Bacillariophyceae is dominant followed by chlorophyceae and myxophyceae. 5 species of Bacillariophyceae 4 species of chlorophyceae and 3 species of myxophyceae were recorded. Microfauna were domiiiated by Protozoan (4) and Rotifers (3) species.